2024
DOI: 10.1002/mabi.202400002
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B3 Containing Polymers for Nanodelivery

Prosper P. Mapfumo,
Jana I. Solomun,
Friedrich Becker
et al.

Abstract: Polymeric nanoparticles with an integrated dual delivery system, facilitating controlled release of bioactive molecules and drugs, offer therapeutic advantages. Key design targets include high biocompatibility, cellular uptake, and encapsulating efficiency. In this study, we synthesized a diverse polymer library derived from niacin, a vitamin B3 integral to metabolic pathways and therapeutics. The library comprised poly(2‐(acryloyloxy)ethyl nicotinate), poly(2‐acrylamidoethyl nicotinate), and poly(N‐(2‐acrylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…This phenomenon can be attributed to AAEN, as its homopolymer nanoparticles demonstrated a similar enhancement of cellular metabolism. 39 Additionally, this effect was similarly more pronounced with AAEN compared to AEN. Surprisingly, C1 was notably cytotoxic.…”
Section: H Nmr and Sec Plots Of All Polymers)mentioning
confidence: 95%
See 4 more Smart Citations
“…This phenomenon can be attributed to AAEN, as its homopolymer nanoparticles demonstrated a similar enhancement of cellular metabolism. 39 Additionally, this effect was similarly more pronounced with AAEN compared to AEN. Surprisingly, C1 was notably cytotoxic.…”
Section: H Nmr and Sec Plots Of All Polymers)mentioning
confidence: 95%
“…In our previous study, PAAEN demonstrated superior attributes in both encapsulation and cellular uptake when compared to PAEN. 39 Therefore, to further explore the potential applications of niacin-derived polymers as gene carriers, a copolymer library was conducted following initial investigations into the transfection efficiency of the A and B series, which resulted in the identification and selection of the optimal ratio. Analysis of molar mass distributions of the polymers using SEC revealed monomodal distributions, as depicted in Figure 1B.…”
Section: H Nmr and Sec Plots Of All Polymers)mentioning
confidence: 99%
See 3 more Smart Citations